Genomic research in Zambia: confronting the ethics, policy and regulatory frontiers in the 21st Century. Issue 1 (December 2015) - Chanda-Kapata, Pascalina; Kapata, Nathan; Moraes, Albertina; Chongwe, Gershom; Munthali, James
Abstract Genomic research has the potential to increase knowledge in health sciences, but the process has to ensure the safety, integrity and well-being of research participants. A legal framework for the conduct of health research in Zambia is available. However, the ethical, policy and regulatory framework to operationalise genomic research requires a paradigm shift. This paper outlines the current legal and policy framework as well as the ethics environment, and suggests recommendations for Zambia to fully benefit from the opportunity that genomic research presents. This will entail creating national research interest, improving knowledge levels, and building community trust among researchers, policymakers, donors, regulators and, most importantly, patients and research participants. A real balancing act of the risk and benefits will need to be objectively undertaken.